Desempeño de las funciones ejecutivas en adultos mayores con diabetes mellitus tipo I y II: revisión sistemática - Luis Hernández, Diana Katerine; Sepúlveda Parra, Paola Andrea (Universidad Antonio Nariño, 2021)
The present documentary review aims to investigate the performance of executive functions in older adults between the ages of 65 and 90 with Type I and II Diabetes Mellitus, for this purpose they were used in databases such as: Nature, Science Direct, Scopus and Journals; locating information from different countries.